2014
DOI: 10.1016/j.geoforum.2013.10.003
|View full text |Cite
|
Sign up to set email alerts
|

Time for a systematic review: A response to Bassett and Fogelman’s “Déjà vu or something new? The adaptation concept in the climate change literature”

Abstract: This critical review debates the issues raised in Bassett and

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 24 publications
0
15
0
Order By: Relevance
“…A systematic literature review approach was used to identify relevant literature pertaining to adaptation policy and practice in hotspot countries according to explicitly formulated criteria as outlined in supplementary materials and building upon recent methodological advances on the use of systematic reviews in an environmental change context Biesbroek et al in press;Ford and Pearce 2010;Lesnikowski et al 2011;Lorenz et al 2014;McDowell et al in press;McLeman 2011) (also see Berrang-Ford et al in this special edition). Full details on the review protocol and procedures are found in supplementary materials.…”
Section: Data Collectionmentioning
confidence: 99%
“…A systematic literature review approach was used to identify relevant literature pertaining to adaptation policy and practice in hotspot countries according to explicitly formulated criteria as outlined in supplementary materials and building upon recent methodological advances on the use of systematic reviews in an environmental change context Biesbroek et al in press;Ford and Pearce 2010;Lesnikowski et al 2011;Lorenz et al 2014;McDowell et al in press;McLeman 2011) (also see Berrang-Ford et al in this special edition). Full details on the review protocol and procedures are found in supplementary materials.…”
Section: Data Collectionmentioning
confidence: 99%
“…In reviewing the state of the climate change vulnerability field, the paper contributes to a growing body of environmental change scholarship that seeks to systematically and transparently assess the state of knowledge in a given area , Lorenz et al 2014, McDowell et al 2014, Porter et al 2014, Sud et al 2015. Such review work is of particular importance for the vulnerability scholarship, where rapid increases in publishing across disciplines have made it difficult for individual researchers and research teams to keep abreast of key developments.…”
Section: Introductionmentioning
confidence: 99%
“…Systematic reviews are especially useful in synthesizing current knowledge and they are transparent in their methods (Berrang-Ford et al 2015;Lorenz et al 2014). We systematically reviewed selected climate change literature following the methodology suggested by Berrang-Ford et al (2015).…”
Section: Methodsmentioning
confidence: 99%
“…First and foremost, the sample of the studies between the reviews differs. Our review was systematic and we selected articles using systematic searches as recommended by Lorenz et al (2014), while Bassett and Fogelman (2013) chose four journals and used only one search word: adaptation. The article search process was different and our search words could have favored contextual vulnerability or mixed-focus studies.…”
Section: Analysis Of the Vulnerability Contextmentioning
confidence: 99%